Criminality in context : the psychological foundations of criminal justice reform - Haney, Craig (Psychology, crime, and justice series., 2020)
"In this groundbreaking book, Craig Haney argues that meaningful and lasting criminal justice reform depends on changing the public narrative about who commits crime and why. Building on decades of research and work at the front lines of the criminal justice system, Haney debunks what he calls the "crime master narrative"--The widespread myth that crime is the simple product of free and autonomous "bad" choices-an increasingly anachronistic view that cannot bear the weight of contemporary psychological data and theory. He meticulously reviews evidence documenting the ways in which a person's social history, institutional experiences, and present circumstances powerfully shape their life course, with a special focus on the role of social, economic, and racial injustice in crime causation. Based on his comprehensive review and analysis of the research, Haney offers a carefully framed and psychologically based blueprint for making the criminal justice system fairer, with strategies to reduce crime through proactive prevention instead of reactive punishment"--